Communicating the “Race” for the COVID-19 Vaccine: An Exploratory Study in Newspapers in the United States, the United Kingdom, and Brazil - Massarani, Luisa; Neves, Luiz Felipe Fernandes (Frontiers in Communication, 2021)
The search for an effective solution to control the COVID-19 pandemic has mobilized an unprecedented effort by science to develop a vaccine against the disease, in which pharmaceutical companies and scientific institutions from several countries participate. The world closely monitors research in the area, especially through media coverage, which plays a key role in the dissemination of trustful information and in the public's understanding of science and health. On the other hand, anti-vaccine movements dispute space in this communication environment, which raises concerns of the authorities regarding the willingness of the population to get vaccinated. In this exploratory study, we used computer-assisted content analysis techniques, with the WordStat software, to identify the most addressed terms, semantic clusters, actors, institutions and countries in the texts and titles of 716 articles on the COVID-19 vaccine, published by The New York Times (US), The Guardian (UK) and Folha de São Paulo (Brazil), from January to October 2020. We sought to analyze similarities and differences of countries that stood out by the science denialism stance of their government leaders, reflecting on the severity of the pandemic in these places. Our results indicate that each newspaper emphasized the potential vaccines developed by laboratories in their countries or that have established partnerships with national institutions, but with a more politicized approach in Brazil and a little more technical-scientific approach in the United States and the United Kingdom. In external issues, the newspapers characterized the search for the discovery of a vaccine as a race in which nations and blocs historically marked by economic, political and ideological disputes are competing, such as the United States, Europe, China and Russia. The results lead us to reflect on the responsibility of the media to not only inform correctly, but also not to create stigmas related to the origin of the vaccine and combat misinformation.